THE CORRELATION BETWEEN VOCABULARY MASTERY AND DESCRIPTIVE WRITING ABILITY OF THE TENTH GRADE STUDENTS - Dewa Made Mahardika Dwijanatha; Dewa Ayu Ari Wiryadi Joni; Ni Wayan Krismayani (Journal on Studies in English Language Teaching (JOSELT), 2022)
The study is aimed at finding the correlation between vocabulary mastery and descriptive writing ability of the tenth-grade students. It aims to find out whether there is a significant correlation or not between students’ vocabulary mastery and descriptive writing ability. This present study used 33 samples of the tenth-grade students. The researcher used tests to collect the data of vocabulary mastery and descriptive writing ability. The technique of analysing the data by using SPSS version 25.0 for Mac. The result of the analysis data showed that the coefficient correlation (r) was 0.716, with the level of significance was 0.000. It indicated that there was a positive significant correlation between vocabulary mastery and descriptive writing ability of the tenth-grade students.